Man and nature: an Islamic perspective - Abdul Razak, Mohd Abbas (2015)
The topic on man and nature is one that has been discussed over the centuries. This topic has caught the attention of many scholars that come from many diverse field of specialization. As an appreciation to the great contribution of nature to the human survival, some have equated nature to God. Since the two are synonymous to them, they worship nature alongside with God. Others thought that nature is an obstacle to the human lives and men need to conquer and prevail over nature. In the light of these two extreme positions, this paper intends to explore and investigate the relationship between man and nature from the Islamic perspective. Apart from that, this paper would like to find out as to why the Muslim community is not paying due attention to the conservation and preservation of nature at a time when there is a serious call made by others to stop the ongoing environmental degradation that is happening all over the world. It is hoped that an investigation of this nature would bring to light as to what should be the ideal relationship of man with nature from the Islamic perspective.